One‐Step Synthesis of a [20]Silafullerane with an Endohedral Chloride Ion1. (4th March 2015) - Tillmann, Jan; Wender, Josef Heinrich; Bahr, Ute; Bolte, Michael; Lerner, Hans‐Wolfram; Holthausen, Max C.; Wagner, Matthias
Abstract Silicon analogues of the most prominent carbon nanostructures, namely, hollow spheroidals such as C60 and the fullerene family, have been unknown to date. Herein we show that discrete Si20 dodecahedra, stabilized by an endohedral guest and valence saturation, are accessible in preparative yields through a chloride‐induced disproportionation reaction of hexachlorodisilane in the presence of tri(n‐butyl)amine. X‐ray crystallography revealed that each silicon dodecahedron contains an endohedral chloride ion that imparts a net negative charge. Eight chloro substituents and twelve trichlorosilyl groups are attached to the surface of each cluster in a strictly regioregular arrangement, a thermodynamically preferred substitution pattern according to quantum‐chemical assessment. Our results demonstrate that the wet‐chemical self‐assembly of a complex, monodisperse Si nanostructure is possible under mild conditions starting from simple Si2 building blocks.